2022
DOI: 10.1038/s41467-022-31103-y
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of the mechanosensor PIEZO1 in glucose-induced insulin secretion in pancreatic β-cells

Abstract: Glucose-induced insulin secretion depends on β-cell electrical activity. Inhibition of ATP-regulated potassium (KATP) channels is a key event in this process. However, KATP channel closure alone is not sufficient to induce β-cell electrical activity; activation of a depolarizing membrane current is also required. Here we examine the role of the mechanosensor ion channel PIEZO1 in this process. Yoda1, a specific PIEZO1 agonist, activates a small membrane current and thereby triggers β-cell electrical activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Support for this comes from recent literature findings, which have found that mechanosensitivity is an integral feature of rod photoreceptors and its possible role in retinal GCL damage. , Consistent with these reports, studies also suggest that T1DM rats have an exaggerated mechanoreflex, which was attenuated by blocking mechano-gated Piezo channels; similarly, inhibition of Piezo1 protected against thrombosis in a type 2 diabetes mellitus setting . Ye and co-worker recently established the role of Piezo1 as an important physiological regulator of insulin secretion. While iron is an essential ion for life, its overload, called “hemochromatosis”, can cause serious damage to various vital organs and is known to accelerate DC and DR. , Among the most well-known are the signaling pathways regulating hepcidin and retinal renin angiotensin system (RAS) involved in retinal and hepatic iron overload leading to organ damage. , On the other hand, disruption of the blood–aqueous barrier leads to iron overload in the lens that comes from the intraocular fluids .…”
Section: Discussionmentioning
confidence: 99%
“…Support for this comes from recent literature findings, which have found that mechanosensitivity is an integral feature of rod photoreceptors and its possible role in retinal GCL damage. , Consistent with these reports, studies also suggest that T1DM rats have an exaggerated mechanoreflex, which was attenuated by blocking mechano-gated Piezo channels; similarly, inhibition of Piezo1 protected against thrombosis in a type 2 diabetes mellitus setting . Ye and co-worker recently established the role of Piezo1 as an important physiological regulator of insulin secretion. While iron is an essential ion for life, its overload, called “hemochromatosis”, can cause serious damage to various vital organs and is known to accelerate DC and DR. , Among the most well-known are the signaling pathways regulating hepcidin and retinal renin angiotensin system (RAS) involved in retinal and hepatic iron overload leading to organ damage. , On the other hand, disruption of the blood–aqueous barrier leads to iron overload in the lens that comes from the intraocular fluids .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ACSF3 protein is a malonyl-CoA that could be used for de novo fatty acid synthesis in mammalian mitochondria [ 49 ]. PIEZO1 plays a critical role via intracellular accumulation of glucose metabolites and regulating insulin secretion [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pdx1 regulates early pancreas formation and insulin secretion, mitochondrial metabolism, and cell survival of β-cell [42]. Piezo1 is essential for glucose-stimulated insulin secretion in β cells [43]. NeuroD1 directly activates genes required for β-cell maturation and function [44].…”
Section: Discussionmentioning
confidence: 99%